Short-term effects of the smoke-free legislation on haemostasis and systemic inflammation due to second hand smoke exposure - Cayla, Guillaume; Sie, Pierre; Silvain, Johanne; Brugier, Delphine; Cambou, Jean-Pierre; Thomas, Daniel; Pena, Ana; O’Connor, Stephen A.; Bura, Alessandra; Ruidavets, Jean-Bernard; Montalescot, Gilles; Collet, Jean-Philippe (Thrombosis and Haemostasis, 2011)
It was the objective of this study to assess the effect of the implementation of the smoke-free legislation on haemostasis and systemic inflammation in second-hand smoking (SHS)-exposed healthy volunteers. Fibrin-rich clot properties, platelet reactivity and inflammatory biomarkers were measured before and four months following the implementation of the smoke-free legislation in gender and age-matched healthy volunteers exposed (n=23, exposed) and unexposed (n=23, controls) to occupational SHS. The primary objective was to compare fibrin-rich clot stiffness before and after implementation of the smoke-free legislation. There was 40% reduction in fibrin-rich clot stiffness following the implementation of the smoke-free legislation in SHS-exposed volunteers (17 ± 7 vs. 10.6 ± 7 dynes/cm², before and after, respectively, p=0.001). These dramatic changes were associated with a 20% reduction in fibrin fiber density (p<0.01) and a 20% reduction inclot lysis time (p=0.05). No change in fibrin properties was observed in the control group of SHS-unexposed volunteers related to the implementation of the smoke-free legislation. Of interest, neither platelet reactivity nor systemic inflammatory biomarkers were changed in either group. The smoke-free legislation is associated with significant changes in fibrin-rich clot properties toward a less thrombogenic conformation with a better fibrinolysis response while neither platelet reactivity nor systemic inflammatory biomarkers are modified. These improvements may explain the observed reduction in acute coronary syndrome following the implementation of the smoke-free legislation.
Keywords: Second hand smoke; smoke-free legislation; fibrin-clot; platelet reactivity; inflammatory biomarkers